Public relations and feminist activism: strategic consensual persuasion or propaganda? - Naíde, Müller (2023)
The global threat to democratic ideals and fundamental rights and freedoms requires that citizens critically assess the diff erences between consensual forms of persuasion and non-consensual, manipulative, and propagandistic forms of persuasion in order to make free and informed choices. Based on an ethnographic work with a Portuguese women’s rights organization during six months (January-June 2021), this paper analyses the intersection of activist public relations and organized persuasive communication within feminist campaigns. Propaganda appears a multi-layered sociological phenomenon and the communication campaigns analyzed in this study indicate that, in principle, feminist activist communication can operate within the realm of strategic consensual persuasion and not on propaganda. Findings also illustrate the possible contributions of public relations for social mobilization, civic participation, and democratic adhesion. Observations showed that not all types of persuasion are harmful or false, and that propaganda does not only serve to change opinions but often intends to maintain dominant trends and the status quo.